The impact of monoallelic inactivation mutations in the ENPP1 gene on pediatric skeletal development: a case report and literature review - Lu, Siyi; Sun, Ning; Li, Yuan; Wu, Zongyi; Zhang, Jingdong (Frontiers in Endocrinology, 2025)
BackgroundRecently, in our clinical work, we discovered a case of abnormal bone metabolism in children resulting from an inactivated mutation of the ENPP1 gene. Through this discovery, we highlighted the impact of the ENPP1 gene on the skeletal growth and development of children, and provided new ideas for the clinical diagnosis of bone diseases in children.Case summaryA 17-year-old boy presented with abnormal gait and hip pain. The anteroposterior (AP) pelvis X-ray revealed bilateral abnormalities in the femoral metaphysis, acetabulum, and ilium bones, as well as slippage of the left femoral head epiphysis. After genetic testing was carried out, it was found that the patient had a monoallelic inactivation mutations in the ENPP1 gene, which is the pathogenic gene of Autosomal-Recessive Hypophosphatemic Rickets 2 (ARHR2). Genetic testing identified that the patient had an inactivating mutation in the ENPP1 gene, which is associated with Autosomal-Recessive Hypophosphatemic Rickets 2 (ARHR2). Since symptoms were present at the time of diagnosis, the current treatment plan includes symptomatic treatments, such as calcium supplementation and femoral epiphyseal fixation.ConclusionWe discovered that the inactivating mutation of the ENPP1 gene has an influence on bone metabolism, particularly calcium and phosphorus metabolism, which can lead to severe adverse effects on the growth and development of pediatric patients. Through this case and a review of the literature, we aim to enable clinical physicians to establish a holistic perspective during pediatric consultations.